(untitled) (Journal of Pakistan Orthopaedic Association, 2015)
Fractures in the proximal femoral area are usually difficult to treat as they consist of hard cortical bone with an inherent slower healing rate than the metaphyseal area, and mechanically the deforming forces are high. Moreover these fractures are usually the result of a high energy trauma and so the integrity of peri fracture soft tissue is affected seriously also. In the elderly osteoporosis makes such fractures more prone to fixation failure, mal-union and nonunion. Over the period of time various implants have been used to fix these fractures with variable results. However since the advent of minimally invasive surgery and implants like proximal femoral nails, gamma nails, reconstruction nails etc the shift seems to be towards these procedures rather open reduction and internal fixations. On similar lines image assisted closed indirect reduction on a fracture traction table followed by fixation with reconstruction nail was done in our study to see the results of this mode of fixation. In twenty eight patients (21 males: 7 females) and age range of 21-70 years, Russell- Taylor reconstruction titanium nailing was carried out from Jan 2013 to Dec 2013. All patients were followed up clinic-radio logically for one year. The outcomes of this technique were retrospectively evaluated using the Harris hip score and variables like infection, nonunion, malunion and implant failure. Based on the results of our study we found Russell-Taylor reconstruction nail a very useful device in high-energy comminuted proximal femoral fractures in providing a bio-mechanically stable fixation.